Assessment of Training Needs of Self Help Group Members - MonikaWason , Premlata Singh , RN. Padaria, K. Vijayaragavan (Indian Journal of Extension Education, 2022)
A study was conducted to identify the training needs of members of Self Help Groups (SHGs) with the sample of 290 members drawn randomly fromCoimbatore district of Tamil Nadu, Prakasham district ofAndhra Pradesh, Puri district of Odisha and Nalanda district of Bihar. Based on overall mean scores across the states, the major training needs in area of enterprise uptake were food processing and seed production, while decision-making, planning, time management, team building, and accounting were the important training needs in descending order under enterprise management. Uses of modern communication technology assumed first rank for Bihar, while second rank for the members of Andhra Pradesh andOdisha.